The design, pedagogy and practice of an integrated public affairs leadership course. Issue 1 (March 2017) - Sandfort, Jodi; Gerdes, Kevin
Current world events demand public affairs leadership training that generates among professionals a sense of capability, agency, and responsibility to engage in complex public problems. In this paper, we describe a unique course operated in the US focused on achieving these learning outcomes. It uses an unconventional schedule and course design that leverages information communication technologies to support learning. Its integrated model combines conventionally distinct courses with a pedagogical approach stressing experiential learning, personal reflection, and critical thinking. The paper describes the teaching practices used in the course, as well as offers three sources of evidence about what results from its implementation.